Edukasi Potensi Kewirausahaan pada Remaja Karang Taruna di Desa Sukatani - Dina Mellita; Andrian Noviardy; Efan Elpanso; Heriyanto Heriyanto; Abdul Aliun Hakim (Lembaga Pengembangan Kinerja Dosen, 2025)
It is very important to teach young people to become entrepreneurs, especially in rural areas that have local economic potential but have not been properly managed. The purpose of this community service activity is to increase the awareness, knowledge, and entrepreneurial skills of Karang Taruna youth in Sukatani Village, Banyuasin Regency. The community service program was designed using a participatory approach, which included entrepreneurship workshops, digital marketing training, identifying business opportunities based on local resources, and obtaining assistance to develop simple business plans. Interactive lectures, group discussions, practical simulations, and participant comprehension assessments were all methods used to implement the methodology. The results of the activities showed a significant increase in participants' knowledge of basic entrepreneurship concepts. They also became more capable of analyzing and identifying local business opportunities and acquired practical skills to market products through various digital platforms. Participants also showed increased motivation and confidence to start their own businesses. This program demonstrates that entrepreneurship education can help rural youth improve their lives, promote economic independence, and support sustainable local economic growth. It is hoped that these findings will serve as a model for implementing similar programs in other rural areas.